IMPROVING STUDENT'S ENGLISH VOCABULARY USING PICTURE AT THE FOURTH YEAR OF SDN 3 JENENGAN BOYOLALI IN 2010/2011 ACADEMIC YEAR - Marhusari, Ayu (2011)
This research is intended to know whether or not the implementation of the technique using pictures improves the students' vocabulary mastery and the strength and weaknesses of teaching English using pictures in teaching-learning English at the elementary school. The problem in this research focuses on the fourth grade students' low vocabulary mastery in English learning at the elementary school. Picture is an appropriate medium, related to the elementary school students' characteristics as the young learners. Picture can be used to improve the students' enthusiasm to learn English vocabulary. This research is a classroom action research carried out at SDN 3 Jenengan Boyolali. In this research, the writer takes the fourth grade students as the subject of the research. There are two cycles in this classroom action research. The steps of each cycle consist of identifying the problem, planning the action, implementing the action, observing the action, reflecting the action, and revising the action. The data are taken from observation in the classroom and interview with the English teacher and the fourth year students of SDN 3 Jenengan Boyolali. Based on the research finding, it can be concluded that the use of pictures can improve the elementary students' achievement in learning English, especially in vocabulary.